अजीत फते नायक रायसा : बघेलखण्ड का आल्हा - Mohapatra, Durga Prasad (Madhya Pradesh Hindi Granth Academy, 2007)
The book describes the bravery of Raysa who is known as Aalha of Baghelkhand.
Ajeet Phate Nayak Raysa : Baghelkhand Ka Aalha
Keywords: Folk Song; Hindi; Hindi